THE USE OF THINK PAIR SHARE STRATEGY IN READING COMPREHENSION - Marnina Marnina; Margaretha F Narahawarin; Ranta Butarbutar (Universitas Musamus, 2020)
The research aimed to find out whether TPS (Think-Pair-Share) strategy can improve the students’ achievement and interest in learning reading and to find out the students’ ability in reading using TPS strategy. This research was done in SMP Yapis Merauke. The population of this research was the students of seven grade SMP Yapis Merauke, academic year 2018/2019. The number of the population was 40 students with 21 boys and 19 girls, while the number of the samples was 40 students have taken purposively sampling. The data were collected by using test, questionnaire and observation. The data from the test and questionnaire were analyzed quantitatively while the data from the observation were analyzed qualitatively. The result of the analysis show that TPS (Think-Pair-Share) strategy can give improvement on students’ reading comprehension ability. The mean score of pretest 45,83 (poor) to to 66,94 (good) in post-test. The finding from questionnaire verifies that the highest rank of the mean score is 43,0 % agreed students; 22,25 % strongly agreed students; 15,25 % of neutral answer and 17,5 % of disagreed students and 2,0 % students answer the strongly disagree statement. TPS (Think-Pair-Share) strategy is responded positively by the students’s reading class and the application is accepted. Keywords: Think-Pair-Share strategy; achievement; interest; reading comprehension